GloMIP Communication Strategy - Paguirigan, Neale Marvin (International Rice Research Institute, 2024)
This compilation of communication collaterals highlights the value of the Global Market Intelligence Platform (GloMIP) in enhancing breeding programs through its strategic use of market intelligence. The Platform plays a pivotal role in supporting market segmentation and product design, enabling more targeted and impactful breeding initiatives. Additionally, it generates critical insights that align with the CGIAR's five impact areas, offering valuable opportunities for advancing agricultural innovation. By fostering evidence-based decision-making, the GloMIP empowers stakeholders to optimize breeding strategies, ensuring they are more responsive to market needs and development goals. This report emphasizes the Platform's potential to drive transformative change in agricultural research and development, promoting sustainable solutions that address global challenges.